Strategi Bimbingan Kelompok Dengan Teknik Self Management Untuk Meningkatkan Motivasi Belajar Siswa Kelas XI SMA Negeri 6 Pandeglang Tahun Ajaran 2025/2026 - oktaviani; Devi Nurul Fikriyani; Muhamad Ikhsan (Universitas Veteran Bangun Nusantara, 2025)
Learning motivation is the drive from both internal and external sources of students that makes them enthusiastic about learning, striving to achieve achievements, and able to overcome obstacles in the learning process. The research design used in this study is the